How does petty corruption affect tax morale in sub-Saharan Africa? An empirical analysis - Björn Jahnke (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
Revenues from taxation gain importance to finance economic development in sub-Saharan Africa. Extortion of bribes by public officials can provide one obstacle for tax compliance. This paper uses micro-level data from the Afrobarometer to analyse how petty corruption erodes tax morale. A mediation analysis shows that petty corruption directly reduces tax morale but also diminishes trust in the tax department and hence indirectly affects tax morale. The effect on tax morale is more severe in countries and regions where fewer people are affected by petty corruption and becomes insignificant if extortion of bribes is particularly prevalent.
Keywords: D73; H26; K42; F63; 330; corruption; tax morale; economic development; mediation analysis; regional disaggregation